PENDAPATAN USAHATERNAK SAPI PERAH ANGGOTA KPS BOGOR (KASUS : KUNAK CIBUNGBULANG DAN KELURAHAN KEBON PEDES) - Leo Rio Ependi Malau; Ratna Winandi (Forum Agribisnis, 2017)
The development of integrated dairy farm area or “KUNAK” in Cibungbulang is one of the government’s efforts to integrate the scattered farmers in Bogor City because the separated farming system has caused a lot of technical, social and economical problems. The farmers relocation process to KUNAK Cibungbulang was not completely succeed. One of the existing dairy farm who managed to keep their business in the city of Bogor was located in Kebon Pedes. This research aimed to analyse the structure of costs, revenue and income of dairy farm business in KUNAK Cibungbulang and Kebon Pedes. The analysis method that used in this research is descriptive and quantitative approach including analysis of income and R/C Ratio. The result showed that the income of dairy farmers from Kebon Pedes is higher than the farmers from KUNAK Cibungbulang. Dairy farmers at Kebon Pedes have to think about the long term consequence of their business, considering that the farm located on densely populated area. One of the alternative is to relocate the farm to KUNAK Cibungbulang.